PROSPEK INDUSTRI TENUN ULOS DI KABUPATEN TOBA SAMOSIR - Sondang Daniel Aritonang; Zulkarnaini '; Syapsan ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in Toba Samosir against employers Ulos weaving. This study aims to determine whether a predicament Ulos weaving industry has good prospects in the future in Toba Samosir .The population in this study amounted to 404 entrepreneurs with a sample of 61 samples of 15% of the population is 60.6 rounded to 61 units of household enterprises using random sampling method by considering the closeness between the researcher and the sample (business unit). The data used is derived from primary and secondary data is obtained from the BPS and the Department of Industry and Commerce, Toba Samosir regency. The method used is descriptive analysis of data collection to answer questions regarding the status of current research on this subject and Financial Feasibility Analysis including, Net Present Value, Benefit Cost Ratio, and Internal Rate Of Return descriptive data are generally collected through data collection methods interview or observation. The survey results revealed that based on calculations performed by using the Net Present Value, Benefit Cost Ratio, Net Benefit Cost Ratio and Internal Rate Of Return it can be concluded that the weaving business Ulos viable and has good prospects in the future because it will encourage increased incomes for entrepreneurs this ulos weaving.Keywords : WeafingUlos, prospects , employment , income , investment